'I couldn't tell such things to others': trauma-exposed youth and the investigative interview. (2nd January 2017) - Langballe, Åse; Schultz, Jon-Håkon
Abstract: Although investigative interviews of persons exposed to traumatic stress are often conducted shortly after the traumatic event, few studies have investigated how these victims experience the interviews. In this study, 320 survivors of the July 2011 massacre at Utøya, Norway, were interviewed face to face and answered a questionnaire about their experiences of the investigative interview. Qualitative, inductive analyses were conducted and descriptive statistics collected. Whereas 72.6% did not perceive the investigative interview as stressful, 27.4% felt it was partly or considerably stressful. Three interrelated factors were identified to impact whether investigative interviews can lead to positive experiences or to increased mental stress and possible harm: whether victims were able to provide a detailed and coherent narrative; whether they experienced the interview as two-way communication; and how and to what extent the investigative interview made sense to them. Practical consequences for improving quality of care for trauma-exposed adolescents in the investigative interview are indicated.